OPC UA versus ROS, DDS, and MQTT: Performance Evaluation of Industry 4.0 Protocols - Profanter, Stefan; Tekat, Ayhun; Dorofeev, Kirill; Rickert, Markus; Knoll, Alois (IEEE International Conference on Industrial Technology (Online), 2019)
Ethernet-based protocols are getting more and more important for Industry 4.0 and the Internet of Things. In this paper, we compare the features, package overhead, and performance of some of the most important protocols in this area. First, we present a general feature comparison of OPC UA, ROS, DDS, and MQTT, followed by a more detailed wire protocol evaluation, which gives an overview over the protocol overhead for establishing a connection and sending data. In the performance tests we evaluate open-source implementations of these protocols by measuring the round trip time of messages in different system states: idle, high CPU load, and high network load. The performance analysis concludes with a test measuring the round trip time for 500 nodes on the same host.